Interface Modification Enabled by Atomic Layer Deposited Ultra‐Thin Titanium Oxide for High‐Efficiency and Semitransparent Organic Solar Cells. Issue 12 (14th October 2020) - Duan, Leiping; Sang, Borong; He, Mingrui; Zhang, Yu; Hossain, Md Anower; Rahaman, Md Habibur; Wei, Qingya; Zou, Yingping; Uddin, Ashraf; Hoex, Bram
Abstract : Organic solar cells (OSCs) are considered to have reached a second golden age with profoundly improved power conversion efficiency (PCE) and device stability in recent years. The modification of the interface layer plays a significant role in achieving performance enhancement in OSCs. Herein, the use of the atomic layer deposition (ALD) ultrathin TiO x to modify the interface layer in OSCs is reported. The modification with only two TiO x ALD cycles not only effectively passivates the interface between the ZnO electron transport layer (ETL) and the active layer, but also reduces the series resistance and improves the charge transport process in the device. An absolute 1% increase in PCE with enhanced device stability for modified OSCs is achieved. Semitransparent OSCs are also fabricated by applying this interface modification strategy. The modification with two TiO x ALD cycles increases the electrical device performance without affecting the optical properties of the semitransparent device. An average PCE of 10.46% with an average visible transmittance (AVT) of 19.61% and a color rendering index (CRI) close to 100 is demonstrated for the fabricated semitransparent device with the modification. The ALD‐assisted interface modification provides a straightforward way to realize high‐performance semitransparent OSCs. Abstract : The use of the atomic layer deposition (ALD) ultrathin TiO x to modify the interface layer in both opaque and semitransparent organic solar cells is reported. The modification effectively passivates the interface, reduces the series resistance, and improves the charge transport, which leads to increased power conversion efficiency (PCE) with enhanced stability in the device.